Field resistance to spinosad in western flower thrips Frankliniella occidentalis (Thysanoptera: Thripidae) - Dong-gang LI; Xiao-yong SHANG; Stuart Reitz; Ralf Nauen; Zhong-ren LEI; Si Hyeock Lee; Yu-lin GAO (Journal of Integrative Agriculture)
The western flower thrips, Frankliniella occidentalis, is one of the most destructive sucking pests of vegetables, fruits and ornamental crops in China. Spinosad is one of the most commonly used insecticides to manage thrips. To assess the incidence of spinosad resistance in F. occidentalis field populations in eastern China, survival rates for 24 different populations were compared with those of a susceptible laboratory strain. All populations showed significantly higher resistance to spinosad compared with the control as determined by comparing median lethal concentrations. Two populations from Shouguang and Liaocheng in Shandong Province were classified as having moderate and high levels of resistance to spinosad with a mean resistance ratio of 17.0 and 89.2, respectively. Our research indicates a widespread reduction in spinosad efficacy for controlling F. occidentalis field populations, and that resistance management strategies should be implemented as soon as practicable, to reduce the potential of progressive resistance development and loss of efficacy.